ASUHAN KEBIDANAN KOMPREHENSIF PADA NY.N USIA 29 TAHUN G2P1A0 DIWILAYAH KERJA PUSKESMAS MAOS - Rini Rochayati; Ellyzabeth Sukmawati; Yuli Sya’baniah K; Norif Didik Nur Imanah; Dahlia Arief Rantauni (Lembaga Pengembangan Kinerja Dosen, 2022)
One indicator of the state’s health status is the decrease in the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR). Central Java Province in 2020 the MMR is 98,60 per 100.000 live births and the IMR is 8,2 per 1000 live births. Cilacap Regency MMR and IMR in recent years are still quite high. AKI in 2019 reached 15 cases. With continuous midwifery care from pregnancy to the selection of contraceptives, it is hoped that it will be an effort to reduce MMR and IMR in Indonesia and achieve optimal maternal and child health. The writing of this final project is in the form of a case study using a midwifery process approach using 7 steps of Varney and SOAP. The results of this study were obtained by Mrs. N during her pregnancy, she was in good health, the delivery process was normal, the puerperium involution was running normally, the baby was not jaundiced and was walking normally, and on family planning counseling the mother chose a 3-month injectable contraceptive. The conclusion of this study the author has applied continuous midwifery care to Mrs. N which is marked by the mother having followed all the recommendations, the mother’s complaints during pregnancy are resolved, the mother gives birth at a health facility, the postpartum period is running normally, the baby’s condition is normal, and the mother chooses a shhort-term contraceptive method.